Board of Director Characteristics and Financial Distress in the ASEAN Region: The Moderating Role of Sustainability Committee - Damayani, Fitri; Fuadah, Luk Luk; Yuniarti, Emylia (Dinasti Publisher, 2026)
This research is motivated by the emergence of the Covid-19 pandemic, which has caused a crisis for companies in various business sectors, potentially leading to financial distress. Board of director characteristics such as gender diversity, education, and tenure can be important aspects in navigating difficult circumstances. The sustainability committee is also a much-needed committee and is expected to strengthen board characteristics in mitigating financial distress. This study uses a quantitative approach with secondary data from 202 companies in the ASEAN region for the period 2020-2024. Data analysis was conducted using panel data regression, a moderated regression analysis, and robust standard error with the assistance of Eviews 12. The results show that gender diversity and education have no significant effect on financial distress, while tenure positively affects financial distress. The sustainability committee cannot moderate the effect of gender diversity and tenure on financial distress but can weaken the positive effect of education on financial distress. These findings indicate that financial distress can be reduced when the board of directors implements its intellectual insights together with the sustainability committee. However, companies should be wary of the average director tenure because it has the potential to increase financial distress.